2016
DOI: 10.1002/sctm.16-0199
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Torn Avascular Meniscal Cartilage Using Undifferentiated Autologous Mesenchymal Stem Cells: From In Vitro Optimization to a First-in-Human Study

Abstract: Meniscal cartilage tears are common and predispose to osteoarthritis (OA). Most occur in the avascular portion of the meniscus where current repair techniques usually fail. We described previously the use of undifferentiated autologous mesenchymal stem cells (MSCs) seeded onto a collagen scaffold (MSC/collagen‐scaffold) to integrate meniscal tissues in vitro. Our objective was to translate this method into a cell therapy for patients with torn meniscus, with the long‐term goal of delaying or preventing the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 67 publications
1
88
0
1
Order By: Relevance
“…In humans, US has been reported to be a valid alternative to magnetic resonance imaging in the assessment of meniscal extrusion (Papalia et al, ). Ovine mesenchymal stem cells/collagen scaffold was tested in a sheep meniscal cartilage tear model (Whitehouse et al, ); different repair techniques have also been tested (Scotti, Hirschmann, Antinolfi, Martin, & Peretti, ) such as stem cells seeded into scaffolds, cell‐free scaffolds, gene therapy, intraarticular delivery of progenitor cells, biological glues, and partial and total tissue engineered meniscus replacement. Meniscectomy and induction of meniscal tears can be performed on medial (Gruchenberg, Burkhardt, Read, & Bellenger, ) and lateral (Beveridge, Shrive, & Frank, ) meniscus in the sheep (Little et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, US has been reported to be a valid alternative to magnetic resonance imaging in the assessment of meniscal extrusion (Papalia et al, ). Ovine mesenchymal stem cells/collagen scaffold was tested in a sheep meniscal cartilage tear model (Whitehouse et al, ); different repair techniques have also been tested (Scotti, Hirschmann, Antinolfi, Martin, & Peretti, ) such as stem cells seeded into scaffolds, cell‐free scaffolds, gene therapy, intraarticular delivery of progenitor cells, biological glues, and partial and total tissue engineered meniscus replacement. Meniscectomy and induction of meniscal tears can be performed on medial (Gruchenberg, Burkhardt, Read, & Bellenger, ) and lateral (Beveridge, Shrive, & Frank, ) meniscus in the sheep (Little et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These data may also help guide decision making on the optimal storage and transport conditions for future clinical trials, similar to analysis of stress variables 3 and clinical application models demonstrated in other studies. [14][15][16] While it is difficult to predict whether the variability seen in this in vitro study would have clinical consequences to patients who receive cell therapy products, suboptimal storage conditions and high variability in cell dosage should be avoided whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Direct intra-synovial injections of MSCs have also been employed and meniscal regeneration and resolution of pain recorded [135,141]. MSCs sourced from a number of tissues including synovial tissues [142][143][144][145], adipose [146,147], bone marrow [45, [148][149][150]] and blood vessels [151] have been applied in a number of applications to promote meniscal repair [44-48, [152][153][154][155][156][157][158] (Table 1). Co-cultures of meniscal cells and MSCs have also been examined in meniscal repair strategies [43, 159,160].…”
Section: Use Of Mscs and Chondrocytes For Meniscal Repairmentioning
confidence: 99%